Job satisfaction as indicator which contributes to high turnover among employees at Metrojaya Midvalley, Kuala Lumpur / Nor Nadirah Zahari - Zahari, Nor Nadirah (Faculty of Business Management, 2006)
Although Job Satisfaction and Motivation had been discussed by many researchers and many theories and concepts were established, yet retailers still need to face high turnover rate. Metrojaya is one of the leading departmental stores in Malaysia. To maintain and increase its efficiency in providing the very best for the customer, it needs to have enough manpower. It is important for any organization to have a good turnover rate or low turnover rate. This is because; it needs a lot of efforts, time and budget in hiring process. Usually organization spends a lot of money in providing training program for its employees. It is such a waste if organization needs to repeat all the process when there is high turnover rate in the organization. Since it is an important factor for organization, therefore the researcher decided to do a study on job satisfaction as indicator which contributes to high turnover at Metrojaya Mid Valley, Kuala Lumpur. This study was to focus on goal of to find out the relationship between job satisfaction and high turnover, and also factors that influence high turnover among employees at Metrojaya Mid Valley, Kuala Lumpur. This study was based on the work itself, pay, supervision, working conditions, co-workers and also high turnover. The scope of study involves 70 respondents, which were randomly picked from employee's name list provided by Metrojaya MidValley, Kuala Lumpur. The questionnaires distributed consist of 3 sections whereby section 8 and section C include items rated on 5-point Likert scale. All data were analyzed by using frequency analysis, Cross Tabulation, and Correlation. The results indicated that job satisfaction has no relationship with high turnover and only the work itself has relationship with high turnover. Several recommendations were suggested to help Metrojaya Mid Valley, Kuala Lumpur to keep its employees satisfy.